The impact of the geographical environment on the hydromorphological conditions of watercourses in southern Poland - Borek, Lukasz (Geology, Geophysics and Environment, 2024)
Hydromorphological assessment of watercourses provides much valuable information about the riverbed and its immediate surroundings, including the influence of geographical environmental factors along with anthropogenic pressures in the catchment area. This paper presents diversity of hydromorphological conditions of 77 sections located on 39 watercourses in southern Poland in three European ecoregions: Eastern Plains, Central Plains and the Carpathians. The study was based on the Hydromorphological Index for Rivers (HIR) method and two sub-indices: Hydromorphological Diversity Score (HDS) and Hydromorphological Modification Score (HMS). Basic and multi-dimensional statistical analyses were performed to identify the main gradients of the geographical environment and the variables that contribute most to the total variability of HIR. The highest mean HIR values were recorded in the Carpathians ecoregion, then in the Central Plains and the lowest in the Eastern Plains, 0.70, 0.67 and 0.58, respectively. Significant differences were found between the Carpathians and Eastern Plains ecoregions in HIR values obtained. Hydromorphological differentiation is most influenced by altitude and geological type. The cluster analysis enabled two main groups of watercourses to be distinguished – the first one was dominated by variables showing HMS > HDS relationship, while the second one was dominated by HDS > HMS relationship. Multi-dimensional analysis provided additional information on the relationships between the variables and the sections studied. The greatest positive impact on the formation of the final HIR value had the variation of the riverbed slope and natural morphological elements of the bed bottom, while the greatest negative impact on HIR had the transformations observed in spot-check.